Shelf and storage life extension by beeswax coating for 'Pan' lime fruit from two production locations - W. Kumpoun (2018)
© 2018 International Society for Horticultural Science. All rights reserved. Beeswax (6%) was reported to be the suitable formula to prolong shelf life of 'Pan' lime fruit in previous study. The application methods of 6% beeswax coating for 'Pan' lime fruit from two production locations were conducted in this study. Two methods of coating, hand coating and machine coating, were applied for 'Pan' lime fruit from high land (960-1200 m a.s.l.) and low land (43-107 m a.s.l.), compared with control (non-coated) fruit. All fruit were stored at 9 and 25°C. The non-coated fruit showed the greatest weight loss in both storage temperature and both production locations. The hand coated fruit showed slightly lower weight loss than that of the machine coated fruit. The fruit from high land had significantly lower weight loss than that of the fruit from low land during stored at 25°C. Percent of juice, vitamin C, total soluble solids content and titratable acidity from fruit of all treatment were not significantly different. The shelf life at 25°C of non-coated, hand coated and machine coated fruit from low land were 7, 17 and 17 days while the fruit from high land were 17, 26 and 23 days, respectively. Storage life at 9°C of the above treatment of the low land fruit were 23, 38 and 31 days and the high land fruit were 23, 52 and 45 days, respectively. The peel thickness of the fruit from high land was thicker than that of the fruit from low land. The different peel thickness may involve in water loss as well as using beeswax coating.